Legally wed : same-sex marriage and the Constitution - Strasser, Mark Philip, 1955- (Cornell University Press, 1997)
Mark Strasser examines the issue of same-sex marriage in light of contemporary constitutional and domestic relations law, showing why the usual arguments against the state's recognizing such unions are either weak or irrelevant. The Supreme Court has articulated numerous interests promoted by marriage, all of which apply to same-sex as well as opposite-sex couples. According to Strasser, the argument made most frequently to deny recognition to same-sex unions - that marriage exists to provide a setting for the production and raising of children - is in fact a reason to acknowledge such unions. The claim that marriage is for children biologically related to both parents is refuted in the case law, which treats biological and adopted children as legally indistinguishable.